Beauty is in the eye of the beholder - An Experience Report on Evaluating Aesthetics of a Design System for HUDs in EUD Serious Games - Muri, Mariana; Rodrigues, Kamila; Darin, Ticianne (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2023)
Serious games have specific goals beyond entertainment. End-User Development (EUD) tools can enable diverse professionals to develop these games for a target audience. However, they overlook important game requirements like mechanics, interface, and aesthetics. This can result in confusing and disconnected interfaces. This experience report describes the process of design and evaluation of thematic families of reusable and standardized visual component elements for end-user-generated mobile games. The evaluation of user experiences with the perception of aesthetic aspects of the Design System used a semantic differential scale to assess their perceptions and interpretations. The results demonstrated good acceptability of the families while also suggesting improvements in typography, shapes, and color palette to improve mood communication. These results are discussed under the perspective of how aesthetic elements influence people’s perception of game interfaces produced for a serious purpose, possibly impacting the player experience.